2015
DOI: 10.1007/s13204-015-0493-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and study of antibacterial activity of spray pyrolysed ZnO:Al thin films

Abstract: Aluminum-doped zinc oxide (ZnO:Al) thin films were deposited onto glass substrates using spray pyrolysis technique with the substrate temperature of 400°C. X-ray diffraction analysis indicated that the films were polycrystalline with hexagonal wurtzite structure preferentially oriented along (002) direction. Surface morphology of the films obtained by scanning electron microscopy showed that the grains were of nanoscale size with porous nature for 6 at.% of Al. Atomic force microscopy observations revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Finally, the structure was modified to spherical particles with a high aggregation and a diameter of about 22-32 nm. These results are in agreement with those of earlier works [29][30][31]. Figure-5 explains the transmittance spectra for the prepared samples.…”
Section: Resultssupporting
confidence: 92%
“…Finally, the structure was modified to spherical particles with a high aggregation and a diameter of about 22-32 nm. These results are in agreement with those of earlier works [29][30][31]. Figure-5 explains the transmittance spectra for the prepared samples.…”
Section: Resultssupporting
confidence: 92%
“…It was found that the intensity of the (002) peak of Al-doped ZnO NSs was comparatively lower than that of pure ZnO NWs, which could reduce the surface energy of ZnO as Al replaced the Zn ions of the hexagonal wurtzite structure. 31 It was evident from the XRD pattern of Al-doped ZnO NSs that the peaks at 31.83 and 36.38° corresponded to the (100) and (101) reflections, respectively, which indicated that the Al-doping could influence the orientation of ZnO nanostructure from the x -axis changing to isotropic. 32 On the other hand, the (002) peak of ZnO NSs was significantly shifted to the larger diffraction angle when compared to pure ZnO NWs because of the replacement of Zn 2+ ions (ion radius 0.74 Å) by smaller Al 3+ ions (ion radius 0.53 Å).…”
Section: Resultsmentioning
confidence: 96%
“…. The zone of inhibition clearly shows the method of the biocidal activity of the Aluminium doped ZnO that obliterates the external wall of the bacteria and promotes death [29]. The antibacterial effect of Al doped zinc oxide was superior on E.Coli than other strain.…”
Section: Optical Propertiesmentioning
confidence: 95%
“…Since then, ZnO particles start to discharge oxygen species into the bacteria that suppress the development of cell which results in the alteration and leakage of the cell and makes the cell to death[28]. The zone of inhibition clearly shows the method of the biocidal activity of the Aluminium doped ZnO that obliterates the external wall of the bacteria and promotes death[29]. The antibacterial effect of Al doped zinc oxide was superior on E.Coli than other strain.…”
mentioning
confidence: 99%